Analisis Strategi Forum Kewaspadaan Dini Masyarakat (FKDM) atas Cegah Dini dalam Penanganan Konflik Sosial di Provinsi Dki Jakarta Tahun 2019 - Agustina, Dwi; Mulyadi, Edy (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
The community is responsible for the implementation of the community early awareness, meanwhile the government is obliged to facilitate it. A good role of the Community Early Awareness Forum or Forum Kewaspadaan Dini Masyarakat (FKDM) followed up by the government can save the community from security threat or disaster and minimize losses by anticipating the security threats and disaster. This research uses qualitative approach. Concept operationalization in this research refers to the used strategy, the SWOT analysis. The FKDM strategies in social conflict early prevention are: 1) inserting early warning system by increasing institutional capacities which include three elements; government, private sector, community through dialogue, 2) National Unity and Politics Agency or Badan Kesatuan Bangsa dan Politik (Kesbangpol) of DKI Jakarta actively making dialogue persuasively and finding solution, 3) budgeting of conflict handling according to the Government Regulation gives opportunity to strengthen community resilience to protect the community, encourage community participation, handle social conflict, and preserve local wisdom to maintain peace.